Development of a Validated RP-HPLC Method Using Full Factorial Design for the Analysis of Ramipril - Hossain, Md Jahid; Shill, Diponkor Kumar; Das, Sreedam Chandra; Ahmed, Khondoker Shahin; Hossain, Hemayet; Kumar, Uttom (Dhaka University Journal of Pharmaceutical Sciences, 2024)
The primary objective of this study is to develop and optimize a simple, novel, reproducible, and efficient RP-HPLC method using quality by design (QbD) approach for the routine analysis of ramipril. The chromatographic separation was carried out by C18 column with an isocratic elution of a mobile phase of 65:35 (%v/v) acetonitrile: water at a flow rate of 0.9 mL/min. The detection was done at a wavelength of 210 nm using a photo-diode array plus (PDA+) detector. A 32 full-factorial design was employed for the development of analytical method using Design Expert® software in which the mobile phase composition and flow rate were taken as independent variables and the retention time (RT), tailing factor (TF) and theoretical plate count (TP) were chosen as responses of the study. Statistically significant models were obtained for the development of the method (p<0.05). The empirical responses perfectly fitted to that of predicted, with an error within the tolerance of ± 2%. This indicates that the model efficiently identified the optimum levels of independent variables, i.e. the composition of mobile phase and its flow rate, to get the desirable responses. The validation of the developed method followed the ICH Q2 (R1) guidelines, demonstrating that the method is robust and well-suited for the routine analysis of ramipril in active pharmaceutical ingredients and in drug products. Dhaka Univ. J. Pharm. Sci. 23(1): 93-102, 2024 (June)